Analysis of Logistics Costs and Dwelling Time on Distribution - Tohir, Muhammad; Primadi, Andri; Naufal Rizqullah, Adilio (Siber Journal of Transportation and Logistics, 2024)
"The Influence of Logistics Costs, Logistics Regulations, and Dwelling Time on Distribution: A Literature Review". The purpose of this scholarly article is to build hypotheses regarding the impact of independent variables on dependent variables, which will be used in future research. The research objects are drawn from online media sources such as Google Scholar, Semantic Scholar, Elsevier, Zotero, and other online journals. The research method involves qualitative descriptive analysis based on e-books and scholarly journals. The article's findings are as follows: 1) Logistics costs have an impact on distribution. 2) Logistics regulations affect distribution. 3) Dwelling TIME influences distribution.